Comparison of Weight Loss, Ghrelin, and Leptin Hormones After Ligation of Left Gastric Artery and Sleeve Gastrectomy in a Rat Model - Yardimci, Erkan (Med Sci Monit, 2017)
BACKGROUND: Ligation of the left gastric artery (LLGA), which supplies the fundus of the stomach, may reduce the appetite hormone ghrelin, resulting in weight control. The aim of this study was to compare LLGA and sleeve gastrectomy (SG) in terms of postoperative outcomes in a rat model. MATERIAL/METHODS: Fifteen male Wistar albino rats, weighing >350 grams (range 350–525 grams), were enrolled in LLGA (N=5), SG (N=5), and control (N=5) groups. Blood samples were drawn preoperatively and also during the first and fourth week postoperatively to assay ghrelin and leptin hormone levels. Body weight was measured in each group. RESULTS: The maximum reduction in ghrelin level (41.5%) was found in the LLGA group. Considerable% total weight loss (TWL) (mean 24.1%) was observed in the SG group, and slight%TWL was noted in the control and LLGA groups (means of 0.1% and 2.1%, respectively). There was no significant difference in mean percent weight change between the LLGA and the SG groups (p=0.08). Blood sample analysis revealed no statistically significant changes in ghrelin or leptin levels between the groups (p=0.9 and p=0.3, respectively). CONCLUSIONS: We present evidence that LLGA causes the same reduction in ghrelin hormone levels as SG at 4 weeks after surgery in a rat model. However, LLGA did not cause the same%TWL as SG. The mechanism of weight loss in SG is most likely due to restriction and to the effects of the procedure, rather than due to neurohormonal changes.